2005
DOI: 10.1007/s10641-005-2925-x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution, Feeding and Body Condition of Four Small Fish Species in the Near-shore and Central Areas of Liangzi Lake, China

Abstract: SynopsisSmall fish abundance is usually high in heavily vegetated habitats in Yangtze lakes, China. Visual and swimming barriers created by dense macrophytes beds could reduce feeding efficiency and growth of small fishes. We tested the hypothesis that small fishes in habitats with dense macrophytes would show decreased feeding efficiency and reduced growth rates by comparing feeding efficiency (measured as the relative weight of fore-gut contents), total length, and condition factor of four small young-of-the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…1 & 5). Our results are consistent with findings in lakes along the middle and lower reaches of the Yangtze River, including Liangzi Lake (Xie et al 2005) and Biandantang Lake (Xie et al 2000, Zhang 2005, where the 2 species are native. Both gobies shifted their diet by feeding increasingly on macrozoobenthos as they grew.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…1 & 5). Our results are consistent with findings in lakes along the middle and lower reaches of the Yangtze River, including Liangzi Lake (Xie et al 2005) and Biandantang Lake (Xie et al 2000, Zhang 2005, where the 2 species are native. Both gobies shifted their diet by feeding increasingly on macrozoobenthos as they grew.…”
Section: Discussionsupporting
confidence: 91%
“…section of intestine from the esophagus to the posterior end of the first loop) were removed and preserved in 75% ethanol (Xie et al 2000(Xie et al , 2005. Food items in non-empty foreguts (77.8% of the foreguts) were counted individually in a counting chamber and subsequently identified to the lowest possible taxonomic level under a dissecting microscope.…”
Section: Gut Content Analysesmentioning
confidence: 99%
“…Results in the present study suggested that vegetation cover is essential to maintain small fish diversity and abundance in shallow lake. However, over-vegetated habitat was demonstrated to result in low feeding efficiency and poor growth of both small fishes and piscivorous fishes (Miranda et al, 1997;Xie et al, 2005). Further studies should be conducted to investigate the effects of macrophyte cover on predator-prey interactions, and to provide the basis for vegetation management and development of a reasonable piscivorous fish stocking strategy in such lakes.…”
Section: Discussionmentioning
confidence: 99%
“…Maintenance of macrophyte cover is essential for high diversity and abundance of small fishes, and hence fishery yield of piscivorous fishes. On the other hand, it is also essential to regulate the level of macrophyte abundance, as other studies indicated that dense vegetation could result in low feeding efficiency and poor growth of both small fishes and piscivorous fishes (Colle and Shireman 1980;Miranda and Pugh 1997;Xie et al 2005). Further studies are needed in future to investigate the effects of macrophyte cover on predatorprey interactions of fish, and to assess ecosystem consequences of the stocking of piscivorous fishes into the Yangtze lakes.…”
Section: Implications For Lake Fishery Managementmentioning
confidence: 99%